Canine Squamous Cell Carcinoma: a Review of 17 Cases - handrashekaraiah, Girish B.; Rao, Suguna; Munivenkatappa, Byregowda S.; Mathur, Kotrappa Y. (Brazilian Journal of Veterinary Pathology, 2011)
Cancer, a fatal malignant disturbance of growth is one of the major causes of mortality in canines. Of the many neoplasms that are known to affect dogs, squamous cell carcinoma (SCC) is relatively more common and highly malignant. In the present investigation, 138 cases of tumor or tumor like growths were evaluated and 17 squamous cell carcinomas (SCC) encountered were studied in relation to its occurrence in population, age, sex, breed, gross appearance, location of the lesion, cytological findings, histological observations and immunoreactivity to cytokeratins. Cytological smears revealed large number of malignant squamous cells occurring either individually or in clusters exhibiting pleomorphism, anisokaryosis and anisocytosis. Well differentiated forms, histologically showed cords or nests of proliferating neoplastic cells consisting of immature polyhedral cells at the periphery and eosinophilic lamellated keratin pearls at the centre. The moderately differentiated ones were characterized by proliferating cells forming cords or nests of cells separated by thin fibrous stroma. The varying intensity of immunostaining observed to 34E12 raised against high molecular weight cytokeratins (1, 5, 10 and 14) correlated well with cellular differentiation with high expression in well differentiated and less in poorly differentiated SCC.